Stanovsko gledališče v Ljubljani v sezoni 1832/33 pod taktirko Eduarda Neufelda in Heinricha Börnsteina - Žigon, Tanja (Ars et humanitas, 2025)
The present paper continues the authors’ prior research on the history of the theatre in Slovenia, focusing the German-language Estates Theatre in Ljubljana in the early 1830s and more specifically on the 1832/33 season, which was managed by the impresarios Eduard Neufeld and Heinrich Börnstein. The season’s repertoire is reconstructed on the basis of two surviving theatre journals as well as theatre posters from the National Museum of Slovenia’s collections. The journals, which were prepared by members of the ensemble, contain not only lists of performances but also information on the troupe, anecdotes and literary vignettes, while the posters provide additional details about titles, authors, genres and casts. Although the journals are more reliable, the posters help provide a fuller picture of the theatre’s repertoire practices. The paper first Tanja Žigon, Tone Smolej / STanovSkogledališčev ljubljanivSezoni 1832/33 ...181outlines the biographies and work of the two impresarios on the Ljubljana stage, then discusses selected plays from the season and reconstructs the complete repertoire. Special attention is given to the difficulties the impresarios faced in leasing the Estates Theatre, the specificities of the ensemble, and the challenges posed by the repertoire they conceived and brought before the Ljubljana audience
Keywords: Börnstein, Heinrich; Estates Theatre in Ljubljana 1832/33; gledališka zgodovina; igralska zasedba; impresarija; Neufelda, Eduarda; Stanovsko gledališče v Ljubljani 1832/33; theatre directors; theatre ensembles; theatre history